2016
DOI: 10.1186/s12877-016-0389-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent peripheral arterial disease and inflammatory burden

Abstract: BackgroundStrong evidence implicates inflammation in the development of atherosclerotic heart disease but less is known about peripheral arterial disease (PAD). Our objective was to test the hypothesis that a composite index of inflammatory burden is associated with PAD.MethodsCross-sectional analysis of a randomly-selected group of 903 community-dwelling men in the MrOS cohort recruited between 2000 and 2002. Using blood samples, we measured seven cytokines and related these levels to prevalent PAD (ankle-bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
1
11
0
2
Order By: Relevance
“…It has also been shown that NOX2-derived ROS production in the extracellular space is in fact increased in vascular disease [ 23 ]. Atherogenic molecules such as tumor necrosis factor α (TNF-α), cholesterol, and homocysteine, which have all been shown to be significantly elevated in PAD [ 102 , 103 ], increase endothelial NOX2 expression [ 23 ]. Furthermore, these molecules lead to clustering of lipid raft domains, which causes NOX2 aggregates to form in the plasma membrane [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that NOX2-derived ROS production in the extracellular space is in fact increased in vascular disease [ 23 ]. Atherogenic molecules such as tumor necrosis factor α (TNF-α), cholesterol, and homocysteine, which have all been shown to be significantly elevated in PAD [ 102 , 103 ], increase endothelial NOX2 expression [ 23 ]. Furthermore, these molecules lead to clustering of lipid raft domains, which causes NOX2 aggregates to form in the plasma membrane [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are key inflammatory cells that are involved at every phase of atherosclerosis, from its genesis to plaque rupture or erosion. Recent studies found that PAD was associated with increased levels of local proinflammatory cytokines, some of which were known to be linked to CAD progression [20][21][22]. A previous study showed that the severity of coronary atherosclerosis was related to the degree of inflammatory response in the affected PAD limb [23].…”
Section: Oct Findingsmentioning
confidence: 99%
“…It is rapidly emerging as a significant global socio-economic burden and currently affects over 202 million people ( 2 ). PAD is associated with significant cardiovascular morbidity and mortality ( 3 ), plus a severely diminished quality of life ( 4 ). PAD is most commonly a result of atherosclerosis and, as such, risk factors for the development of the disease include smoking, diabetes mellitus (DM), hypertension ( 5 ), and advanced age ( 6 ).…”
Section: Introductionmentioning
confidence: 99%